Relapse of NPM1-Mutated AML with Extramedullary Manifestation 17 Years after Allogeneic Hematopoietic Stem Cell Transplantation - Braune, Jan; Rieger, Kathrin; Blau, Olga; Keller, Ulrich; Bullinger, Lars; Krönke, Jan (Case Reports in Hematology, 2022)
The majority of patients with acute myeloid leukemia (AML) with the NPM1 mutation achieve remission with intensive chemotherapy. However, many patients subsequently relapse, which occurs frequently within the first 2–3 years after therapy, while late relapse after more than 10 years is rare and can also represent secondary/therapy-associated AML without the NPM1 mutation. Here, we present a case of NPM1-mutated AML that developed medullary and extramedullary relapse 17 years after allogeneic stem cell transplantation, maintaining the NPM1 mutation and all other genetic alterations detected at first diagnosis. This exceptionally long latency between diagnosis and relapse of a genetically highly related leukemic clone implies the existence of therapy-resistant, persisting dormant leukemic stem cells in NPM1 mutant AML.